Tumor-Associated CD68+, CD163+, and MARCO+ Macrophages as Prognostic Biomarkers in Patients With Treatment-Naïve Gastroesophageal Adenocarcinoma - Jeremiasen, Martin; Borg, David; Hedner, Charlotta; Svensson, Maria; Nodin, Björn; Leandersson, Karin; Johansson, Jan; Jirström, Karin (Frontiers in Oncology, 2020)
Background Despite improvements in surgical methodologies and perioperative chemo- and radiotherapy, the prognosis for patients with esophageal and gastric cancer remains poor. Hence, there is a great need to identify complementary biomarkers for improved treatment stratification. Tumor-infiltrating immune cells have been shown to impact on outcome in many types of cancer, including gastroesophageal cancer. The aim of this present study was to examine the prognostic value of tumor-infiltrating macrophages in gastroesophageal adenocarcinoma. Methods The density of CD68+, CD163+ and MARCO+ macrophages was assessed by immunohistochemistry on tissue microarrays with primary tumors from a consecutive, retrospective cohort of 174 patients with treatment-naïve gastroesophageal adenocarcinoma. Total densities and infiltration in tumor nest (TN) were denoted as none/sparse (0), intermediate (1), or high (2). The impact on overall survival (OS) was examined by Kaplan-Meier analysis, log-rank test and Cox proportional hazards modelling. Results Increased infiltration of both CD68+ and CD163+, but not MARCO+, macrophages in TN was significantly associated with a stepwise reduced survival. Median OS for patients with none/sparse, intermediate and high CD68+ TN infiltration was 4.4, 2.6 and 1.0 years, respectively. Median OS for patients with none/sparse, intermediate and high CD163+ TN infiltration was 4.4, 2.2 and 1.1 years, respectively. High infiltration of CD68+ macrophages remained an independent prognostic factor in adjusted analysis (hazard ratio 1.61, 95% confidence interval 1.02-2.55, p=0.041). Conclusion Infiltration of CD68+ and CD163+, but not MARCO+, macrophages is prognostic for OS in gastroesophageal adenocarcinoma. The relevance of this finding in clinical practice remains to be elucidated.